BLACK SME’S AND COVID-19: A SOUTH AFRICAN PERSPECTIVE ON RISKS IN THE AUTOMOTIVE INDUSTRY AND WHY THOSE RISKS SHOULD BE MANAGED - Peterson, Denis Desmond; Chinyamurindi, Willie (Journal of Management Small and Medium Enterprises (SMEs), 2024)
The research identifies risks (and response to this) that Black-owned Small and Medium Enterprises (SMEs) in the automotive industry face in South Africa. The context is a business environment affected by the COVID-19 pandemic. Semi-structured interviews were used for the study with a sample of 11 businesses (6 micro-businesses and 5 small businesses). All the businesses were based either in the Gauteng Province or Eastern Cape Province of South Africa. Thematic analysis was used to analyze the collected data. The findings highlight the vulnerability of Black SMEs in the face of the Covid-19 pandemic through a set of factors inherent in the business environment. The participating Black SMEs narrated their response to the shocks created by the identified set of factors. The findings of the study provide vital information for policymakers, business leaders, and other stakeholders, to create contingencies, policies, and frameworks necessary to support small businesses. Keywords: Small Business; Risk; Covid-19; Automotive Industry